2023
DOI: 10.1111/apce.12423
|View full text |Cite
|
Sign up to set email alerts
|

What are the determinants affecting cooperatives’ profitability? Evidence from Spain

Abstract: This study focuses on the analysis of the determinants of Spanish cooperatives’ profitability. We inspect several variables, whose influence on firms’ profitability has been verified by prior literature, and we assess whether these results are confirmed in cooperatives. The data span 13 years (2008–20). We approach the analysis including: (i) firm‐specific factors, (ii) industry‐specific factors, and (iii) location factors. There is a main research question: Are there significant differences in cooperatives’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 143 publications
1
2
0
Order By: Relevance
“…Increasing profits will have an impact on increasing wealth or increasing company assets. When a company has large assets, the company will have a more stable condition (Pervan & Višić, 2012), and can help the company face risks and strengthen the company's image in the future (Ríos, 2023). This is in line with research by Sudiyatno, Puspitasari, Suwarti, & Asyif (2020) and Ilham, et al (2022).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Increasing profits will have an impact on increasing wealth or increasing company assets. When a company has large assets, the company will have a more stable condition (Pervan & Višić, 2012), and can help the company face risks and strengthen the company's image in the future (Ríos, 2023). This is in line with research by Sudiyatno, Puspitasari, Suwarti, & Asyif (2020) and Ilham, et al (2022).…”
supporting
confidence: 76%
“…Sudiyatno, Puspitasari, Suwarti, & Asyif, 2020). Based on the research results of Lalitha, Sandhyavani, & Sudha (2020),Ríos (2023),Putri & Mutumanikam (2022),Firda & Efriadi (2020), andPervan & Višić (2012), stated that the higher the level of company profitability indicates that the company able to manage company assets optimally in order to maximize company value. So it can be concluded that the fourth hypothesis in this research is as follows.…”
mentioning
confidence: 99%
“…This shift has resulted in a transformation of the role of arable land in agricultural production. With the maturity of agricultural processing technologies and the development of rural e-commerce, the income growth of cooperatives is no longer reliant on expanding scale [37], leading to a continuous reduction in the dependence on arable land. So, in the context of the high-quality development of farmers' cooperatives, does the determinant role of arable land resources still exist?…”
Section: Introductionmentioning
confidence: 99%